PATIENT SAFETY CULTURE IN HOSPITAL ORGANIZATION - Ana Cláudia de Azevêdo Bião e Silva; Darci de Oliveira Santa Rosa (Universidade Federal do Paraná, 2016)
Survey study conducted in May 2015 that described patient safety culture in hospital organization. Of the total 511 nursing professionals, 267 individuals composed the random sample, 128 met the inclusion criteria and answered the questionnaire "Pesquisa sobre Segurança do Paciente em Hospitais" (Survey on Patient Safety in Hospitals), totaling a response rate of 47.94%. Of the safety culture dimensions, the ones which stood out with negative answers were: "Team work in the unit" with 67% (338), "Expectations on your supervisor/boss and actions promoting patient safety" with 66.3% (330), "Organizational learning - continuous improvement" with 53.8% (198) and "Internal transfers and shift changes" with 50.9% (255), representing the main areas with potential for improvement. There were no dimensions with positive overall answers defined with area of strength. It is of utmost importance to share responsibility in implementing strategies aiming to correct weaknesses found to promote qualified, effective and safe health care.